Wear analysis of A356 alloy cast through rheometal process. (12th April 2017) - Gupta, Robin; Sharma, Ashok; Pandel, Upender; Ratke, Lorenz
Abstract: In present investigation, correlation between microstructure, mechanical properties and wear analysis for the non-heat-treated and heat-treated A356 was observed. The rheometal process changed the dendritic morphology into globular morphology which improved the mechanical properties and wear resistance of the alloy. Mechanical properties of non-heat-treated and heat-treated A356 alloy were studied. Wear tests for the non-heat-treated and heat-treated samples were performed. The SEM analysis was employed for microstructural feature of worn surfaces. The results showed that the rheometal process along with the use of baffles, addition of grain refiner and T5 heat treatment showed better mechanical properties and wear resistance of A356 alloy as compared to other processing conditions.